2001
DOI: 10.1016/s0022-2275(20)31676-x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic cholesterol and bile acid metabolism and intestinal cholesterol absorption in scavenger receptor class B type I-deficient mice

Abstract: The scavenger receptor class B type I (SR-BI), which is expressed in the liver and intestine, plays a critical role in cholesterol metabolism in rodents. While hepatic SR-BI expression controls high density lipoprotein (HDL) cholesterol metabolism, intestinal SR-BI has been proposed to facilitate cholesterol absorption. To evaluate further the relevance of SR-BI in the enterohepatic circulation of cholesterol and bile salts, we studied biliary lipid secretion, hepatic sterol content and synthesis, bile acid me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
3
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(36 citation statements)
references
References 72 publications
4
28
3
1
Order By: Relevance
“…Moreover, the LDLR pathway is the main route of hepatocellular cholesterol metabolism, and the expression of LDLR reflects the content of cellular cholesterol. 47 Consistent with the effects of BBR, M3, and A8 on LDLR expression, these 3 compounds could significantly reduce the cholesterol content in HepG2 cells, while M3 and A8 showed better potential effects on cholesterol lowering than BBR. When compared with the effect of several statins (for example atorvastatin, lovastatin, and simvastatin), 48,49 M3 and A8 exhibited similar decrease (30%-40%) on cellular cholesterol content in HepG2 cells.…”
Section: Discussionsupporting
confidence: 61%
“…Moreover, the LDLR pathway is the main route of hepatocellular cholesterol metabolism, and the expression of LDLR reflects the content of cellular cholesterol. 47 Consistent with the effects of BBR, M3, and A8 on LDLR expression, these 3 compounds could significantly reduce the cholesterol content in HepG2 cells, while M3 and A8 showed better potential effects on cholesterol lowering than BBR. When compared with the effect of several statins (for example atorvastatin, lovastatin, and simvastatin), 48,49 M3 and A8 exhibited similar decrease (30%-40%) on cellular cholesterol content in HepG2 cells.…”
Section: Discussionsupporting
confidence: 61%
“…Simultaneous expression of CD36 and CLA-1/SR-BI in the proximal intestine might serve either to guarantee, by acting redundantly, a vital function and/or to allow a fine-tuned modulation of lipid absorption. Interestingly, it has recently been reported that in SR-BI deficient mice, intestinal cholesterol absorption is normal, suggesting the necessity of other molecules able to compensate for the loss of intestinal absorptive activity (Mardones et al 2001). Selective expression of CD36 in the proximal intestine is consistent with the observed regional expression of intestinal genes involved in the absorption of nutrients (lipids and non-lipids) in the diet (Shaw-Smith and Walters 1997).…”
Section: Discussionmentioning
confidence: 61%
“…The role of intestinal SR-BI on cholesterol absorption remains controversial. Studies showing either no effect of SR-BI germline deletion on intestinal cholesterol absorption in mice 15 or minor effects of increasing/knocking down SR-BI levels in CaCo-2 cells 27 and animal models 17 sharply contrast with studies showing high-affinity cholesterol binding in CaCo-2 cells 28 and increased cholesterol absorption after moderate intestinal SR-BI overexpression. 16,29 Herein, we show that, in polarized CaCo-2 cells, SR-BI-cholesterol binding activity is required for insulininduced intracellular lipid accumulation, cholesterol uptake, and apo B-containing lipoprotein secretion, suggesting that SR-BI may be involved in triglyceride rather than cholesterol intestinal absorption.…”
Section: Discussionmentioning
confidence: 92%
“…In mice, SR-BI gene deletion has no apparent effect on intestinal cholesterol absorption. 15 On the contrary, modest transgenic overexpression of SR-BI in enterocytes has been reported to increase cholesterol and triglyceride absorption rates in mice. 16 Nonetheless, these results failed to be replicated in a more recent study.…”
Section: Introductionmentioning
confidence: 99%